Short distance and average absolute distance with wavelet transform for the high impedance fault location in the 11KV distribution underground system / Mohd Syukri Ali - Mohd Syukri, Ali (2013)
In general, high impedance fault (HIF) is a fault when an undesirable contact occurs between a conducting element of a network and a non-conducting object or surface resulting in a very small fault current leaking out. The occurrence of HIF may result an arcing which leads to potential hazards to human life and the environment. Moreover, a significant risk of fire as a consequence of the arcing phenomenon may pose damaging possibility to the power system equipment. On the long run, if HIFs are left untreated, they will affect power system quality in terms of service continuity and energy loss. In order to overcome the problems, power utilities need to locate and isolate the HIF as quickly as possible so that repair works and restoration process of the network can be done in a short period of time. Unfortunately, locating the fault is very challenging especially for a distribution network. This is due to the complexity of the network such as the presence of non-homogeneous line, branches and load variations. Although some HIF location techniques had been proposed, the technique may not be easily adopted due to the high cost of installation and maintenance, the requirement of an effective and reliable data transmitting devices and also a large amount of data that needed to be analysed. Considering the importance of identifying the HIF location in the distribution system, a low cost technique, utilizing minimum data and involving a single measurement point is proposed in this study. The method uses extracted features of three-phase voltage signal and matched with sets of stored features. Two different approaches which are the Shortest Distance and Average of Absolute Difference techniques have been proposed to identify the faulty section. A ranking analysis is introduced to priorities the inspection of the multiple possible faulty sections. The simulation was carried out using the PSCAD/EMTDC software to obtain the fault voltage signal during HIF event. The simulation results show that the proposed method is able to identify the fault location with various fault impedance values. Also, the proposed method is considered effective and economical since the method requires only a single measurement of voltage signal to determine the actual faulty section during the HIF.